Alginate Based Interpenetrating Polymer Network (IPN) in Drug Delivery and Biomedical Applications - Mittal P.; Kapoor R.; Mishra B. (My University, 2025)
Interpenetrating polymer is the type of hydrogels which has gained consideration in the last decade due to their enormous biomedical applications. IPN has proven to be great delivery system for providing sustains release drug delivery. This chapter aims to discuss the basics of IPN, their synthesis procedure, biomedical applications of IPN based on the nature of the network. To provide the controlled release to the formulation, IPN systems are constructed. A number of polymers can be used for the creation of IPN networks, like alginate, chitosen, starch and polysaccharides, protein based polymers. Semi synthetic and synthetic polymers can also be employed for the formulation of the same. IPN posses the properties like biodegradability, biocompatibility and bio erodibility. Apart from being used in drug delivery for sustained release properties, they are also used for the formulation of Scaffolds, implants, burn dressings and wound healing bandages etc. Although the alginates and other polymers have found to be very effective in the synthesis of IPNs, modifications of their bonds can improve their properties like cross linking, erodibility and time for the synthesis of IPNs etc. This chapter summarizes the biomedical applications, advantages of IPNs and different dosage forms based on IPNs. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.